Co-Firing Innovation and Community Empowerment: A Co-Creation Analysis in the Biomass Supply Chain of PT PLN Nusantara Power Pacitan - Nuril Endi Rahman; Rakhma Widya Dharojah; Ferra Wulan Saputri; Maryani Maryani (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
This study examines co-firing innovation and community empowerment through a co-creation analysis within the biomass supply chain at the PT PLN Nusantara Power Generation Unit in Pacitan. Theoretically, this study draws on the service-dominant logic and co-creation perspectives, which emphasize the importance of multi-stakeholder collaboration in creating shared value. A qualitative method with a case study approach was employed. Data were gathered through in-depth interviews, each lasting two hours, with three PLN representatives, two vendors, and three biomass-supplying MSME actors. The results indicate that co-creation practices manifest across three dimensions: co-design (MSME involvement in supply planning), co-production (MSME participation in biomass processing), and co-delivery (distribution based on local partnerships). These practices generate economic benefits through job creation, environmental benefits by reducing carbon emissions from 4 million tons to 330,000 tons per year (equivalent to a 7% post-co-firing reduction), and social harmony rooted in trust and social legitimacy. Consequently, the biomass supply chain in Pacitan serves not only as a technical instrument for energy supply but also as an arena for community empowerment and sustainable social relationship development.Penelitian ini mengkaji inovasi co-firing dan pemberdayaan masyarakat melalui analisis co-creation dalam rantai pasok biomassa di PT PLN Nusantara Power Unit Pembangkitan Pacitan. Secara teoritis, studi ini mengacu pada perspektif service-dominant logic dan co-creation yang menekankan pentingnya kolaborasi multipihak dalam menciptakan nilai bersama. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam yang masing-masing berlangsung selama dua jam bersama tiga perwakilan PLN, dua pihak vendor, dan tiga pelaku UMKM penyuplai biomassa. Hasil penelitian menunjukkan bahwa praktik co-creation terwujud dalam tiga dimensi: co-design (keterlibatan UMKM dalam perencanaan pasokan), co-production (partisipasi UMKM dalam pengolahan biomassa), dan co-delivery (distribusi berbasis kemitraan lokal). Praktik ini terbukti menghasilkan manfaat ekonomi berupa penciptaan lapangan kerja, manfaat lingkungan melalui pengurangan emisi karbon dari 4 juta ton menjadi 330.000 ton per tahun (setara dengan 7% pascapembakaran bersama), serta harmonisasi hubungan yang berlandaskan kepercayaan dan legitimasi sosial. Dengan demikian, rantai pasokan biomassa di Pacitan tidak hanya berfungsi sebagai instrumen teknis penyediaan energi, melainkan juga sebagai arena pemberdayaan masyarakat dan pengembangan hubungan sosial yang berkelanjutan.